Data quality through a web-based QA/QC system: implementation for atmospheric mercury data from the global mercury observation system. Issue 8 (15th July 2015) - D'Amore, Francesco; Bencardino, Mariantonia; Cinnirella, Sergio; Sprovieri, Francesca; Pirrone, Nicola
Abstract : The overall goal of the on-going Global Mercury Observation System (GMOS) project is to develop a coordinated global monitoring network for mercury, including ground-based, high altitude and sea level stations. Abstract : The overall goal of the on-going Global Mercury Observation System (GMOS) project is to develop a coordinated global monitoring network for mercury, including ground-based, high altitude and sea level stations. In order to ensure data reliability and comparability, a significant effort has been made to implement a centralized system, which is designed to quality assure and quality control atmospheric mercury datasets. This system, GMOS-Data Quality Management (G-DQM), uses a web-based approach with real-time adaptive monitoring procedures aimed at preventing the production of poor-quality data. G-DQM is plugged on a cyberinfrastructure and deployed as a service. Atmospheric mercury datasets, produced during the first-three years of the GMOS project, are used as the input to demonstrate the application of the G-DQM and how it identifies a number of key issues concerning data quality. The major issues influencing data quality are presented and discussed for the GMOS stations under study. Atmospheric mercury data collected at the Longobucco (Italy) station is used as a detailed case study.